Expression analysis of five candidate genes in eight contrasting rice genotypes suggest role of Lagging growth and development 1(LGD1), Pinhead1 (PNH1) and Leaf Panicle 2 (LP2) in low light intensity response at vegetative stage - Dutta, Suvendhu S; Tyagi, Wricha; Rai, Mayank (ORYZA-An International Journal of Rice, 2021)
Light acts as an energy source in plants for photosynthesis and also is an environmental cue leading to growth and differentiation. The quality and duration of light is therefore, key to obtaining yield and growth targets. Our previous study in rice led to identification of a panel of contrasting genotypes and putative candidate genes and markers for low light intensity tolerance. In the present study, expression of a set of five candidate genes (LGD1, PNH1, ILA1, CAB2R and LP2) previously identified to be associated with low light intensity tolerance was studied in a panel of eight rice genotypes at two time points post stress induction (one hour and two days). Cumulative normalised expression levels for genes LDG1 and PNH1 were down-regulated in response to one hour low light stress only in susceptible genotypes. While the cumulative normalised expression levels of ILA1 and LP2 genes were down- and up-regulated, respectively in tolerant genotypes. After two days of low light stress, expression of PNH1 and LP2 were down- and up-regulated in tolerant and susceptible genotypes, respectively. Our data suggests that genes LGD1, PNH1 and LP2 can be targeted for achieving vegetative stage low light intensity tolerance. Long term stress followed by recovery experiment revealed genotype Pusa Sugangh-5 as tolerant to low light intensity. These experiments suggest that mechanism of low light intensity tolerance in Pusa Sugangh-5 is distinct from the other four tolerant rice genotypes.